Modelos divergentes de ensino religioso? análise das experiências do RJ e SC - Brito, Lucelmo Lacerda de (2015)
This study aims to analyze the social constructions of the regulatory and implementation experiences of religious education in school systems that correspond to the States of Rio de Janeiro and Santa Catarina, analyzing the tensions between secularization and desecularization of the Brazilian State in the educational setting. The work is justified by the necessity of reflection about the models of religious instruction practised in the country, once that discipline is constitutionally mandatory and touches on a key aspect of Republican freedom: the secularity of the State. The methodology of the work is the analysis of documents, from a corpus that reference includes all the relevant standards, laws, ordinances, decrees, directives, among others; and also records of discussion of the discipline, notably the Conselho de Igrejas para o Ensino Religioso CIER/SC, the Conselho do Ensino Religioso-CONER/SC, the Forum Permanente para o Ensino Religioso - FONAPER and the Assembleia Legislativa do Rio de Janeiro - ALERJ. Our theoretical framework is the social constructivism, Ivor Goodson, who understands the Constitution of the pre-activ curriculum of school subjects as a result of the struggle between the various social groups, and demand to know the story only of those political processes. The thesis defended is that the effective construction of discipline in the States of Santa Catarina and Rio de Janeiro were the result of action of religious denominations, but also for secular movements, with partisan political and academic ballast and the result of these processes were two models with strong Christian traits, but also with many concessions to secular ideals, making the terms applied to the different modes of existence of religious education , which is of "Confessional" Model and "Phenomenological Model", arbitrary terms, who cannot grasp the complexity of each model